2020
DOI: 10.3389/fimmu.2020.01628
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Exposure to Cigarette Smoke Suppresses the Gasotransmitter H2S Biogenesis and the Effects Are Transmitted Transgenerationally

Abstract: Rationale: Gestational cigarette smoke (CS) impairs lung angiogenesis and alveolarization, promoting transgenerational development of asthma and bronchopulmonary dysplasia (BPD). Hydrogen sulfide (H 2 S), a proangiogenic, pro-alveolarization, and anti-asthmatic gasotransmitter is synthesized by cystathionine-γ-lyase (CSE), cystathionine-β-synthase (CBS), and 3-mercaptopyruvate sulfur transferase (3MST). Objective: Determine if gestational CS exposure affected the expression of H 2 S synthesizing enzymes in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 74 publications
(120 reference statements)
0
3
0
Order By: Relevance
“…qRT-PCR was conducted using the Bio-Rad CFX Real-Time PCR detection system. Quantification of the results was performed using the delta-delta (ΔΔ)Ct method and U6 noncoding small nuclear RNA (snRNA) was used as a reference gene for lncRNA expression levels and beta-actin and GAPDH were used for mRNA expression levels as described recently ( 15 ).…”
Section: Methodsmentioning
confidence: 99%
“…qRT-PCR was conducted using the Bio-Rad CFX Real-Time PCR detection system. Quantification of the results was performed using the delta-delta (ΔΔ)Ct method and U6 noncoding small nuclear RNA (snRNA) was used as a reference gene for lncRNA expression levels and beta-actin and GAPDH were used for mRNA expression levels as described recently ( 15 ).…”
Section: Methodsmentioning
confidence: 99%
“…A recent study further found that the expressions of three H 2 S-generating genes, including CSE, CBS, and 3MST, were all lower in the placentas from mothers who smoked during pregnancy in comparison with the mothers who never smoked. Quitting smoking during the first trimester of pregnancy could partially improve the expressions of these H 2 S-generating genes in the placentas [ 52 ]. More studies need to be conducted to validate if the downregulated expressions of these H 2 S-generatiang enzymes might be a biomarker for asthma susceptibility in children.…”
Section: H 2 S and Cigarette Smokingmentioning
confidence: 99%
“…It was found that mouse lung exposed gestationally to cigarette smoking had significantly lower levels of CSE, CBS, and 3MST in both the F1 and F2 generation. Moreover, the lungs from F1 and F2 progenies displayed with impaired angiogenesis and alveolarization, suggesting that a lower level of H 2 S is correlated with the increased risk of lung disorders [ 52 ].…”
Section: H 2 S and Cigarette Smokingmentioning
confidence: 99%